Age-related susceptibility to severe malaria associated with galectin-2 in highland Papuans. - Randall, L; Kenangalem, E; Lampah, D; Tjitra, E; Mwaikambo, E; Handojo, T; Piera, K; Zhao, Z; de Labastida Rivera, F; Zhou, Y; McSweeney, K; Le, L; et al. (2010)
BACKGROUND: Age and host genetics are important determinants of malaria severity. Lymphotoxin-alpha (LTalpha) has been associated with the development of cerebral malaria (CM) and other severe malaria (SM) syndromes. Mutations in genes regulating LTalpha production contribute to other acute vascular diseases and may contribute to malaria pathogenesis. METHODS: We tested the association between rs7291467, a single-nucleotide polymorphism (SNP) in the LTalpha-related gene encoding galectin-2 (LGALS2), disease severity, and function in a case-control study of ethnic Highland Papuan adults and children with SM (n = 380) and asymptomatic malaria-exposed controls (n = 356) originating from a non-malaria-endemic region but residing in a lowland malaria-endemic area of Papua, Indonesia. RESULTS: The LGALS2 SNP showed a significant association with susceptibility to SM (including CM), in children (odds ratio, 2.02 [95% confidence interval, 1.14-3.57]) but not in adults. In SM, the C allele at rs7291467 was associated with enhanced galectin-2 transcript levels. In a separate group of Tanzanian children originating from a malaria-endemic region, we found preservation of the major ancestral LGALS2 allele and no association with susceptibility to CM. CONCLUSIONS: Results suggest differences in the inflammatory contribution to the development of SM between children and adults in the same population and potential differences between individuals originating from malaria-endemic and non-malaria-endemic areas.